O ensino do som como conteúdo de física para alunos surdos: um desafio a ser enfrentado. - Oliveira, Verônica Rosemary de (2017)
Research on the teaching of sound for the deaf is still preliminary, but they already point to paths that may favor classroom work. This essay aims at contributing to research and discussions on deaf education and the teaching of sound for deaf students in Physics class. Hence, we reflected on certain obstacles faced by these students in the Physics class of state schools in the city of Cascavel/PR, as for the learning of physical concepts related to sound, since they are an audience with specific needs included in a regular school. The objectives of this paper are: (i) to understand deaf education and its nuances, revisiting many different historical moments up to the context of inclusive education, by means of bibliographical studies; to (ii) show the role of teachers and translators/interpreters of Brazilian Sign Language in the teaching of Physics; and (iii) to verify what is the perception deaf students have from the teaching of sounds, as well as what is the duty of a translator/interpreter as a mediator in the classroom, and what ideas Physics teachers make of teaching deaf students the concepts of sound. In order to obtain our answers, we traveled back in time all the way to 2005, taking decree 5.626/2005 into account, which includes the discipline of Brazilian Sign Language in college education courses, where its enforcement was said to be complied with within ten years. Our essay was, therefore, grounded on bibliographical, documental and field research. The bibliographical research was founded on articles, papers, dissertations and other relevant publications on our area of subject. As for the documental research, we utilized relevant documents and laws concerning public policies related to Education, the Teaching of Physics and Inclusive Education. When it came to field research, we ran questionnaires answered by Physics teachers and Brazilian Sign Language translators/interpreters, as well as interviews from deaf students enrolled in state schools and deaf students with a high school degree obtained from 2005 on (2016). As a support for data analysis, besides the theoretical references, we used the techniques for content analysis from Bardin (2016). Outcomes show that the teaching of sound to deaf students in Physics class is intertwined with complex relations from the subjects involved. Data analysis pointed to the need of better team work between the sign language translator/interpreter and the Physics teacher, so they can overcome a few ideas concerning the deaf students' incapacity and go beyong this attitude barrier that was historically built -- the idea that deafness and sound do not match.